Phonetic Spelling of Javanese Speakers in Karangpaten Village - Misbach Maimun Damanhuri; Laili Qotrunnada E.K.P.P; Elis Fatmawati3; Sania Dina Kartika; Dian Luthfiyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
It is undeniable that times are always changing. For this reason, everyone must continue to learn to keep a store of development. The benefit of learning is to provide up-to-date information and news to people. If we don’t know the latest information about what happens the in the world, the younger generations may lead, for instance, in e. This descriptive qualitative study focuses on the description of the English phonetic spelling system spoken by the speakers of JavathJava the backgroundconnotesconotes that such speakers of certain regional backgrounds possess the identic sound and preferential native language. This studescribeption of the phonetic spelling with the Java native language through the phonetic method to the villagers of Karangtapen village Lamongan. In this study, the researchers have three objectives: (a) to know the kinds of consonants and vowels features that are different, (b) to understand the common characteristics of pronunciation, and (c) to distinguish sh the effect of staying in a village and a often going for pronunciation. Keywords: phonetic, spelling, Javanese